Reducing Visit-To-Visit Variability in Systolic Blood Pressure for Improving the Progression of Carotid Atherosclerosis and Endothelial Dysfunction in Patients with Hypertension Management. - Hongbin Song; Zhendong Liu; Yingxin Zhao; Lin Ye; Fanghong Lu; Hua Zhang; Yutao Diao; Jianchao Xu (Tehran University of Medical Sciences, 2014)
Visit-to-visit variability (VVV) in blood pressure (BP) creates challenges to hypertension control and was independent associated with increased all-cause mortality in hypertensive patients. The major goal of the present study was to investigate the association of VVV in systolic (S)BP with progression of carotid atherosclerosis and en-dothelial dysfunction in on-treated hypertensive patients.Overall, 356 hypertensive patients were enrolled and completed the trial. Clinic BP was measured at baseline and at 3 monthly thereafter. Carotid artery ultrasound and endothelial function were evaluated at baseline and annually follow-up visit. VVV in BP was assessed by standard deviation (SD) and coefficient of variation (CV) of serial follow-up BP measurements. The patients were divided into low, middle, and high group by tertile of SD in SBP.Decrease percentage of maximum intima-media thickness (IMT) and stiffness index β and increase percentage of brachial flow-mediated dilation (FMD) and nitric oxide (NO) in lower groups were significant greater than in higher groups (P < 0.05). Change percentage of stiffness index β and endothelin-1 positively, and change percentage of FMD and NO negatively correlated with SD, CV, maximum, and delta of SBP (P < 0.05). SD and CV of SBP were risk factors for change percentage of IMT, stiffness index β, FMD, NO, and endothelin-1 independently of other influential factors, such as age, and mean SBP.Excessive VVV in SBP maybe increase carotid atherosclerosis and impair endothelial function in on-treated hypertensive patients. Reducing VVV in SBP is benefit for patients with hypertension management.